Relationships among gingival crevicular fluid biomarkers, clinical parameters of periodontal disease, and the subgingival microbiota - Teles, R.P. (2010)
BACKGROUND: The objectives were to measure the levels of gingival crevicular fluid (GCF) biomarkers and subgingival bacterial species in periodontally healthy and periodontitis subjects in order to explore relations among these biomarkers, the subgingival microbiota, and clinical parameters of periodontal disease. MATERIAL AND METHODS: Clinical periodontal parameters were measured at 6 sites per tooth in 20 periodontitis and 20 periodontally healthy subjects. GCF and subgingival plaque samples were obtained from the mesiobuccal aspect of every tooth. GCF levels of interleukin-1β (IL-1β), matrix metalloproteinase-8 (MMP-8) and IL-8 were measured using checkerboard immunoblotting and the levels of 40 bacterial taxa quantified using checkerboard DNA-DNA hybridization. A subset of “clinically healthy” (CH) sites from each group was analyzed separately. Significance of differences between groups was determined using the unpaired t-test or the Mann-Whitney test. Correlations among immunological, microbiological and clinical data were determined using the Spearman rank correlation coefficient. RESULTS: There were positive correlations among mean clinical parameters and mean levels of the 3 biomarkers and proportions of Orange and Red complex species (p<0.05). CH sites from periodontitis subjects had higher levels of IL-1β and IL-8 and higher proportions of Orange and Red complex species (p<0.05) than CH sites from periodontally healthy subjects. Red complex species were positively associated with the expression of all biomarkers (p<0.05), while Purple and Yellow complex species had negative correlations with IL-1β and IL-8 (p<0.05). CONCLUSIONS: CH sites from periodontitis subjects present higher levels of GCF biomarkers and periodontal pathogens than CH sites from periodontally healthy subjects. Different microbial complexes demonstrated distinct associations with specific GCF biomarkers.